CAUSE FACTORS IN IMPLEMENTING THE TEACHER LEARNING DIFFICULTIES DOMAIN AFFECTIVE - Rini Pangestuti; Holilulloh Holilulloh; Muhamad Mona Adha (Jurnal Kultur Demokrasi, 2012)
The research objective of this thesis was to determine the factors that influence teachers' difficulties in implementing beranah affective learning in SMP Negeri 4 Sekampung East Lampung. Itated by interest in the author of the importance of affective learning where the goal pebelajaran beranah this can affect the results of cognitive and psychomotor learning . Given the importance of affective learning and the fact that there is a reluctance in applying pembelajran affective teacher at the school, it raises the question of the causes that need to be resolved.This study uses the theory of affective learning, levels of the affective domain, the affective domain measurement, and theory of affective assessment. The method used in this research is descriptive research with a total sample of 20 respondents using a questionnaire, and analysis techniques in this study by using a percentage formula.The results of this study are, so tends internal factors contribute to the cause of the difficulties in implementing the teachers' affective learning as much as 50%, quite a role as much as 30%, and as much as 20%, do not contribute to the cause of learning difficulties in implementing affective teacher at SMP Negeri 4 Sekampung.Ekstren factors also tend to play a role in causing trouble enough teachers in implementing affective learning, development factors are contained in the teacher as much as 50% is quite a role, was instrumental in 30%, and as much as 20%, do not contribute to the cause of learning difficulties in implementing affective teacher. Of socialization factors play a role in causing enough trouble as much as 50% of teachers, 30% very important role, and as much as 20%, do not contribute to the cause of the difficulties in implementing teacher pembelajran of affective and affective factors play an important role Ratings are 50%, 30% is quite a role, and 20% said not contribute to the cause of the difficulties in implementing teacher pembelelajaran beranah affective in SMP N 4 Sekampung East Lampung.Keywords:cause factors, difficulty factors teachers, implementing learning affective domain,